The influence of emotional labour on fatigue: customer complaints and return package as moderators - Claudya, Putri Cindy; Maulana, Wahyu (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2026)
Emotional labour can occur in employees due to emotional demands from the company. This can cause employees to experience Fatigue and will certainly have a negative impact on the company. The purpose of this study is to determine the effect of Emotional Labour on couriers at Ninja Express and also to determine the role of Customer Complaints and Return Package as moderating the relationship between the two. In this study, data collection used questionnaire distribution to the object with 99 couriers involved as a sample determined by purposive sampling technique. Through quantitative analysis, the data that has been collected is processed with the SmartPLS application. The results showed that Emotional Labour positively and significantly affects Fatigue. Customer Complaints do not moderate research on the effect of Emotional Labour on Fatigue. Return Package does not moderate research on the effect of Emotional Labour on Fatigue. The implications of this study suggest that companies provide free counseling services, workshops on handling consumer complaints, and standardization of delivery procedures.